Effect of plasma activated water (PAW) on rocket leaves decontamination and nutritional value. (October 2021) - Laurita, Romolo; Gozzi, Giorgia; Tappi, Silvia; Capelli, Filippo; Bisag, Alina; Laghi, Giulia; Gherardi, Matteo; Cellini, Beatrice; Abouelenein, Doaa; Vittori, Sauro; Colombo, Vittorio; Rocculi, Pietro; et al.
Abstract: Plasma Activated Water (PAW) obtained by exposing water to cold atmospheric pressure plasma, has recently emerged as a promising alternative for food decontamination, compared to the use of traditional chemical sanitizers. The aim of the study was to evaluate the efficacy of PAW treatments for rocket salad decontamination. Washing with PAW for 2, 5, 10 and 20 min was assessed against different endogenous spoilage microorganisms and compared to untreated water and hypochlorite solution. The chemical composition of PAW as a function of treatment and delay time was characterized and the effect on product quality and nutritional parameters was evaluated. Results showed that PAW allowed an average reduction of 1.7–3 Log CFU/g for total mesophilic and psychrotrophic bacteria and Enterobacteriaceae following 2–5 min washing with minimal variation of qualitative and nutritional parameters. Overall, experimental results highlighted the potentiality of PAW treatments as a promising alternative to chlorine having the advantage of a minor adverse impact on environment and consumers' health. Industrial relevance: To meet consumers demand, the minimally processed fruit and vegetable industry needs to find sustainable solutions as alternative to the use of traditional chemical sanitizers that allow to increase product shelf-life and preserve safety, qualitative and nutritional characteristics. Plasma activated water represents a promising strategy for food decontamination, but its effects on foods have been only limitedly investigated. The present research is the first study on the use of plasma activated water on fresh rocket leaves, providing new and important information on microbial inactivation and quality of the fresh cut product. Highlights: Plasma Activated Water was used to reduce the microbial load on rocket leaves. Concentrations of the main reactive species in PAW were analysed. PAW washing was more efficient than hypochlorite against spoilage microbial groups. Only limited changes in product quality and nutritional parameters were observed.